Know Your Enemy: How Unauthorized Repatriated Migrants Learn About and Perceive Anti-Immigrant Mobilization in the United States - Ward, Matthew; Martinez, Daniel E (Migration Letters, 2015)
Recently scholars have turned their attention towards a growing anti-immigrant movement in the United States. In particular, residents called ‘minutemen’ have garnered attention for their vigilante patrols of the U.S.-Mexico border. Yet, there remains an absence of rigorously collected data from the unauthorized migrants they target. Filling this void, we draw on original survey data from wave 1 of the Migrant Border Crossing Study (MBCS) and address three questions: Among unauthorized repatriated migrants who have heard of minutemen, from where do they get their information? What qualities or characteristics do unauthorized repatriated migrants ascribe to minutemen? And, finally, how accurate are these perceptions? In so doing, we detail the composition of unauthorized repatriated migrants’ knowledge networks and the role these played in diffusing knowledge about minutemen. Additionally, we illuminate disparities in the quality of the minuteman-related information these networks diffuse. We find that respondents relied heavily on media outlets in the United States and Mexico to obtain information about minutemen. Social networks and the crossing experience itself mattered to a much lesser extent. Interestingly, unauthorized repatriated migrants were mixed in their perceptions of exactly who minutemen were, and migrants varied greatly in their ability to accurately identify minutemen. We conclude with implications and directions for future research.